Efektivitas Promosi Di Media Sosial Pada Keputusan Pembelian Pelanggan Di Gallery DEWDEW Collection Berdasarkan Model AIDA - Arista Dini Nurhidayanti; Ambar Tri Hapsari; Khoirul Umam (RELASI : JURNAL EKONOMI, 2020)
The purpose of this study is to answer the question of whether the promotion carried out by the Dewdew Collection Gallery is effective in making consumers decide to buy their products. This type of research is quantitative descriptive using cross sectional data that occurred in July 2019. Based on the results of research from 35 respondents samples of consumers with affordable populations, using the Guttman scale and KR 20, obtained information that the Attention dimension of 0.82 which means, promotion can attract attention. Interest dimension of 0.95 which means that promotion can arouse consumer interest to buy. The dimension of the Desire is 0.64. Even though it is not too big, it can be categorized as being able to bring up the desire of consumers to buy. And the Action dimension of 0.79 which means that the promotion has been able to move the consumer's decision to buy. The final result of an average of 4 dimensions of AIDA of 0.8, which means that the promotion carried out by the Dewdew Collection Gallery through online social media as a whole is effective.